Effect of Training Phase on Physical and Physiological Parameters of Male Powerlifters - Daniel A. Hackett; Guy C. Wilson; Lachlan Mitchell; Marjan Mosalman Haghighi; Jillian L. Clarke; Yorgi Mavros; Helen O'Connor; Amanda D. Hagstrom; Gary J. Slater; Justin Keogh; Chris McLellan (MDPI AG, 2020)
Longitudinal research on training and dietary practices of natural powerlifters is limited. This study investigated the effect of phases of training on physical and physiological parameters in male natural powerlifters. Nine participants completed testing at two time points: (i) preparatory phase (~3 months prior to a major competition) and (ii) competition phase (1-2 weeks from a major competition). No significant changes between training phases were found for muscle strength and power. A trend for significance was found for decreased muscle endurance of the lower body (−24.4%, p = 0.08). A significant increase in leg lean mass was found at the competition phase (2.3%, p = 0.04), although no changes for other body composition measures were observed. No change was observed for any health marker except a trend for increased urinary creatinine clearance at the competition phase (12.5%, p = 0.08). A significant reduction in training volume for the lower body (−75.0%, p = 0.04) and a trend for a decrease in total energy intake (−17.0%, p = 0.06) was observed during the competition phase. Despite modifications in training and dietary practices, it appears that muscle performance, body composition, and health status remain relatively stable between training phases in male natural powerlifters.